Well-being of University Students with Special Needs as Viewed by University Teachers in Slovakia - Sirotová, Mariana; Michvocíková, Veronika; Lorenzova, Jitka (Journal of Education Culture and Society, 2025)
Aim. The main objective of the study is to identify the students with the specifics needs as a part of university educational process from the perspective of surveyed university teachers working at Slovak universities. Method. The study was conducted via the questionnaire method. The questionnaire was used to collect data in the quantitative research. It contained close-ended questions and was distributed to the respondents through an online platform. The respondents of the study were 96 university teachers working at Slovak universities. The analysis of the collected data was carried out using the statistical software SPSS 20. Univariate, bivariate and multivariate data analyses were used in the SPSS 20 to analyse the collected data. Results. The submitted text is of a theoretical-empirical character. The theoretical part defines a university teacher and describes the specific needs of students. The empirical part contains the results of our empirical research. The results of the empirical research show that the students with the specifics needs are a part of university educational process. This group of the students must have wellbeing supported. University teachers provide special needs students with suitable specific conditions for the implementation of the educational process, which support the well-being of the mentioned group. Conclusions. The students with the specifics needs are a part of university educational process. According to this, promoting the well-being of students with specific needs should be an essential part of the current higher education process. If a university teacher wants to provide special needs students with specific conditions for the educational process, he/she must be informed in advance of the fact that a student has been given the status of a student with specific needs.